2020
DOI: 10.3390/app10124087
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Wave Nonlinearity on Cross-Shore Sediment Transport in Coastal Zone: Experimental Investigations

Abstract: On the basis of field experiment data, the main features of influence of non-linear wave transformation scenarios on cross-shore sediment transport in coastal zones were investigated. The bottom deformations due to the non-linear wave transformation follow the specific scenario. The increase in the second non-linear harmonic amplitude leads to the erosion of the underwater slope at the distances corresponding to this process, with the subsequent accumulation of sandy material closer to the shore at distances w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…The scheme of the experiment and positions of wave breaking are shown in Figure 1. A more detailed description of the wave regime on that day is given in [1,20,23,24]. For the analysis, we selected chronograms of wave transformation between gauges 9 and 12 (spilling breaking) and 1 and 4 (plunging breaking).…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scheme of the experiment and positions of wave breaking are shown in Figure 1. A more detailed description of the wave regime on that day is given in [1,20,23,24]. For the analysis, we selected chronograms of wave transformation between gauges 9 and 12 (spilling breaking) and 1 and 4 (plunging breaking).…”
Section: Field Experimentsmentioning
confidence: 99%
“…The process of wave breaking is characterized by significant losses of their energy. Changes in the steepness of waves and their asymmetry, occurring both due to linear and nonlinear processes and due to breaking, lead to a change in the higher statistical moments of wave motion, which determine the magnitude and the direction of sediment flow in the coastal zone [1].…”
Section: Introductionmentioning
confidence: 99%
“…During the experiment at the Shkorpilovtsi study site of the Institute of Oceanology of the Bulgarian Academy of Sciences, 15 wire wave gauges were evenly spatially located along the research pier (240 m) and installed at a depth range of 4.5−0.5 m. The free surface elevations at 15 points were synchronously measured at a sampling frequency of 5 Hz. The length of wave records was from 20 min to 1 h. A more detailed description of this field experiment and experimental results concerning irregular wave transformations can be found in [5,8,[15][16][17].…”
Section: Field Experimentsmentioning
confidence: 99%
“…In this case beach erosion will occur because there will be no wave component of sediment transport to the shore and the undertow directed to the sea will prevail. It was shown that the spatially periodic exchange of energy between the first and second harmonics contributes to the formation and movement of underwater sand bars [4,5]. In addition, the periodic exchange of energy between harmonics leads to the arising and disappearance of secondary waves that significantly change the mean wave period [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…During storms, high waves break on the top of bars and cause strong offshore currents ("undertow") that transport the sediment toward the sea, resulting in sand bar migration from the coast and beach erosion [4]. During the attenuation of the storm and decreasing in the heights and periods of the waves, as well as at moderate energy wave conditions, the sediment transport due to wave nonlinearity leads to a gradual migration of sand deposits, accompanied by accumulative processes of beach restoration (for example, [4,5]). In addition to movement on the time scale of individual storms, it has been noted by many researchers that sand bars migrate quasi-periodically depending on the seasonal wave climate during the year [6,7].…”
Section: Introductionmentioning
confidence: 99%